KINERjA WANITA NELAYAN DALAM INDUSTRI RUMAH TANGGA STUDI SOSIAL – EKONOMI MASYARAKAT KOTA SEMARANG - Muji Utami, Santi (Faculty of Social Science, Universitas Negeri Semarang, 2009)
In dealing with employment opportunities for women, empowerment of economic institutions that areÃ‚Â ooted in the community such as domestic industry is a perfect alternative. for its activities in the vicinityÃ‚Â f the home (home - base - production), in their own homes and independent businesses. The writingÃ‚Â was trying to describe the basic capabilities of women fshing, types of household industries, fshing herÃ‚Â ontribution to the family economy, and the constraint factor in obtaining women fshing opportunitiesÃ‚Â n domestic industrial sectorÃ‚Â The method used in this study are qualitative methods using techniques Trianggulasi. Analysis ofÃ‚Â ata using an interactive model analysis The research subject is women who are living in a fshing village,Ã‚Â ocated in the productive age status as wives or widows who became head of the family,Ã‚Â Based on the results and discussion can be concluded that the skills / basic skills that most womenÃ‚Â re based on the experience of fshermen who by his predecessors. The wives of fshermen do the workÃ‚Â n the household sector in the form of marinating, smoking and making Pindang. They also perform otherÃ‚Â obs in general are associated with fshing activities. The fsher women who work at this informal sector,Ã‚Â will increase the household fnances because her husbandÃ¢â‚¬â„¢s income level was not suffcient fulfllment ofÃ‚Â aily life. Women who are involved fshermen earning activities are active actors socio-economic changesÃ‚Â n fshing communities. Factors that hamper the performance of women in the household industry sectorÃ‚Â s the low motivation to develop business, education level is relatively low, and limited capital, abilityÃ‚Â nd skills possessed.Keywords: Seconds merchant, peoples economic, entrepreuneurship